Prognostic value of vasodilator stress perfusion CMR in patients with known myocardial infarction. (8th February 2021) - Pezel, T; Garot, P; Kinnel, M; Landon, V; Hovasse, T; Toupin, S; Unterseeh, T; Morice, MC; Champagne, S; Louvard, Y; Sanguineti, F; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Several studies have demonstrated the consistently high prognostic value of stress perfusion cardiovascular magnetic resonance (CMR). This prognostic value in patients with known myocardial infarction (MI) is poorly described. There remains some skepticism about the capacity of stress CMR in predicting the clinical outcome due to the technical challenge during image analysis causes by myocardial scar. PURPOSE: The aim of our study was to assess the prognostic value of vasodilator stress perfusion CMR in patients with known MI. METHODS: We prospectively included consecutive patients with known MI referred for vasodilator stress perfusion CMR with dipyridamole. They were followed for the occurrence of major adverse cardiovascular events (MACE) defined as cardiac death or recurrent non-fatal myocardial infarction (MI). Univariable and multivariable Cox regressions for MACE were performed to determine the prognostic value of inducible ischemia or late gadolinium enhancement (LGE) by CMR. RESULTS: Of 1602 patients with known MI (68 ± 17 years, 78% men), 1556 (97%) completed the CMR protocol, and among those 1401 (90%) completed the follow-up (median follow-up 5.7 (3.9–7.6) years). Reasons for failure to complete CMR included ECG-gating problems (n = 13), intolerance to stress agent (n = 12), renal failure (n = 12), declining participation (n = 4) and claustrophobia (n = 5). Stress CMR was well tolerated without occurrence of death or severe adverse event. Patients without inducible ischemia experienced a substantially lower annual event rate of MACE (3.1%) than those with 1 or 2 segments of ischemia (4.5%), than those with 3 to 5 segments of ischemia (21.5%), than those with 6 or more segments of ischemia (45.7%, for all p < 0.01). Using Kaplan-Meier analysis, the presence of myocardial ischemia identified the occurrence of MACE (hazard ratio HR 3.52; 95% confidence interval CI: 2.67 – 4.65; p < 0.001). In a multivariable stepwise Cox regression including clinical characteristics and CMR indexes, the presence of inducible ischemia was an independent predictor of a higher incidence of MACE (HR 2.84; 95% CI: 2.14 to 3.78; p < 0.001). CONCLUSION: Stress CMR is technically feasible and has a good discriminative prognostic value to predict the occurrence of MACE in patients with known MI.